Poor Appetite and Dietary Intake in Community‐Dwelling Older Adults - Meij, Barbara S.; Wijnhoven, Hanneke A. H.; Lee, Jung S.; Houston, Denise K.; Hue, Trisha; Harris, Tamara B.; Kritchevsky, Stephen B.; Newman, Anne B.; Visser, Marjolein (Journal of the American Geriatrics Society (JAGS), 2017)
Background/objectives Poor appetite in older adults leads to sub‐optimal food intake and increases the risk of undernutrition. The impact of poor appetite on food intake in older adults is unknown. The aim of this study was to examine the differences in food intake among older community‐dwelling adults with different reported appetite levels. Design Cross‐sectional analysis of data from a longitudinal prospective study. Setting Health, aging, and body composition study performed in the USA. Participants 2,597 community‐dwelling adults aged 70–79. Measurements A semi‐quantitative, interviewer‐administered, 108‐item food frequency questionnaire designed to estimate dietary intake. Poor appetite was defined as the report of a moderate, poor, or very poor appetite in the past month and was compared with good or very good appetite. Results The mean age of the study sample was 74.5 ± 2.8 years; 48.2% were men, 37.7% were black, and 21.8% reported a poor appetite. After adjustment for total energy intake and potential confounders (including biting/chewing problems), participants with a poor appetite had a significantly lower consumption of protein and dietary fiber, solid foods, protein rich foods, whole grains, fruits, and vegetables, but a higher consumption of dairy foods, fats, oils, sweets, and sodas compared to participants with very good appetite. In addition, they were less likely to report consumption of significant larger portion sizes. Conclusion Older adults reporting a poor appetite showed a different dietary intake pattern compared to those with (very) good appetite. Better understanding of the specific dietary intake pattern related to a poor appetite in older adults can be used for nutrition interventions to enhance food intake, diet variety, and diet quality.